ANALISIS WAKTU TEMPUH DAN BIAYA OPERASIONAL KENDARAAN UMUM KONVESIONAL DAN NON KONVESIONAL TUJUAN SAMARINDA - BALIKPAPAN - RAHMAN, ABDUL (KURVA S JURNAL MAHASISWA, 2018)
Travel Time is the time it takes the vehicle to travel the length of the route on its route or the time it takes the vehicle to travel. The purpose of this study is to know the performance assessment of conventional and non conventional vehicles serving the route of Jl. Cendana Samarinda to Sultan Aji Muhammad Sulaiman Airport, Balikpapan City. Speed is a measure of traffic that is generally used as a benchmark of system performance. Basically the speed and travel time can not be separated, considering these two factors are highly related. The faster the speed that a system can provide, the shorter the time it takes to reach the destination Primary data This data retrieval is done by using GPS tool (global positioning system) in the presence of this tool, then the data retrieval becomes very easy because the required data has been recorded on the GPS tool which then connected with the computer program, the data covering the time (date, hour, minute, and, second) data retrieval, vehicle speed per second / per minute and length of surveyed road. The travel time of conventional public transport vehicles from going in vehicles traveling through route r8 to go is 2.50 Minutes and non-conventional vehicles traveling through route r1 - r8 are 2.30 Minutes. Anilisis vehicle operating expenses (BOK) of conventional public transport go through route r1 - r8 with road length = 126,046, kilometers is Rp 440,443, Anilysis of vehicle operational cost (BOK) of non conventional public transport goes through route r1 - r8 with path length = 125,246 kilometer is Rp. 14,555